THE LIBERATION OF IZMIR ACCORDING TO THE TURKISH PRESS - Uğur ÜÇÜNCÜ (Fırat University, 2019)
The occupation of İzmir by the Greeks on 15 May 1919 was important results on the Turks and Greeks. While the Turkish Nation experienced great sadness, Greeks had lived in the happiness of approaching the Megalo Idea. However, because of the occupation of İzmir by Greeks, the Turks showed great reaction against the Greeks. At the same time the occupation increased the desire of the Turkish National Struggle. Under the leadership of Mustafa Kemal Pasha, The Turkish Nation won important victories in Inönü Wars and Sakarya War at the Western Front. Especially after the Turkish victory against the Greek army at Dumlupınar, on 30 August 1922, Greek forces were constantly retreating towards Izmir. Finally İzmir was liberated from the Greek occupation on September 9, 1922, by Turkish army. The İzmir’s liberation was important results on the Turks and Greeks. First of all Greeks were forced to withdraw from İzmir. This situation came to mean the end of the Anatolian adventure for Greeks. While the Greeks experienced great sadness Turkish Nation had lived in the happiness of approaching the ideal of Misak-ı Milli. Press was the best source reflecting the Turkish public at the years of the İzmir’s occupation and liberation. In thıs study are used in the following newspapers reflecting all regions of the Turkey: Hâkimiyet-i Milliye, Babalık, Vakit, İkdâm, Peyâm-ı Sabâh, Şark, Sada-yı Hak, Islahât, Yeni Adana, İstikbâl, Açıksöz, Varlık and Satvet-i Milliye. The archives of the Prime Minister of the Republic, the Institute of the Turkish Revolutionary History, General Staff Military History and Military Strategic Studies Department are also used to support the press. İzmir’s occupation and its results on the Turks and Greeks will be enlightened.